Lesbian texts and contexts: Radical revisions - Jay, Karla; Glasgow, Joanne (Feminist crosscurrents, 1990)
Lesbian writers include some of the most innovative and adventurous writers of this century, but only recently have they been given their due attention in terms of critical study. This book is the first anthology to discuss the subject of lesbianism as it relates to the critical interaction among readers, writers, and literary critics. It explores lesbian texts in terms of identification, meaning, and interpretation, and examines the complex entanglements of identity, voice, intersubjectivity, textualities, and sexualities.
Keywords: amériques; anthologie; approches et analyses; arts; discipline; lesbianisme; littérature; outils; ouvrages de références; personnes lesbiennes; régions géographiques; états-unis; études littéraires